Context of the riverside population of the Municipality of Belém (Research, Society and Development, 2021)
This article addresses the historical aspects of a riverine population that lives on the islands in the municipality of Belém. It also tells, in a summarized way, the process of construction of the daily life of these people and how painful and violent was their experience with the presence of the Portuguese and other people that arrived in the Amazon. The invaders needed slave labor to be able to explore and expand the lands they took as their own in the region, and the Indians, in turn, ended up being a labor force qualified to walk in the forest, in the rivers, and still easy to be enslaved. The study seeks to show that the preservation of the riverside culture demonstrates the resistance of an ecological system and of social traditions brought from father to son, and how this custom is strongly related to the expansion movement of the extractive economy produced on the islands of the city of Belém. And the conservation of this community overlaps the capitalist system of reproducing in space-time.